Kinetics and minimal inhibitory concentrations of ceftiofur in tear film following extended-release parenteral administration (Excede®) in dogs - Bowden, Anna Catherine; Allbaugh, Rachel A.; Smith, Joe S.; Mochel, Jonathan P.; Sebbag, Lionel (Frontiers in Veterinary Science, 2022)
Purpose. Describe the pharmacokinetics of extended-release parenteral ceftiofur (Excede®) in canine tear film and compare these concentrations to minimal inhibitory concentrations (MICs) of ceftiofur against common ocular pathogens in dogs. Methods. Six dogs of various breeds were enrolled. Disruption of blood-tear barrier was achieved with histamine-induced conjunctivitis to ensure clinical relevance of the results. Each dog received a single subcutaneous injection of 5 mg/kg Excede®, followed by tear collection with Schirmer strips at times 0, 0.25, 0.5, 1, 2, 4, 8, 12, 24, 36, 48, 72, 96, 120, 144, 168, 192, 216 and 240h. Drug quantification was performed with liquid chromatography-mass spectrometry. MICs were determined for Staphylococcus pseudintermedius, Streptococcus canis and Pseudomonas aeruginosa by assessing bacterial growth (n = 10 per bacterial species) in the presence of ceftiofur at increasing concentrations. Results. Blood-tear barrier breakdown provided tear film concentrations of ceftiofur 3.2-28.9-fold higher than in the contralateral healthy eye (n = 1 dog, pilot experiment). In all 6 dogs, ceftiofur concentrations in tears varied from 2.3 to 637.5 ng/mL and were detectable up to 10 days (240h) after subcutaneous injection. However, tear levels always remained below MICs for common ocular isolates (≥640 ng/mL). Conclusions. Ceftiofur reached the tear compartment (for up to 10 days) after a single parenteral injection, however tear concentrations were extremely variable and too low to be effective against common bacterial pathogens in dogs. Further studies with different ceftiofur dosage or other long-acting injectable antibiotics are warranted.